With United Forces: How Design-Based Research can Link Theory and Practice in the Transdisciplinary Sphere of CLIL - Silvia Bauer-Marschallinger (Universitat Autònoma de Barcelona, 2019)
This paper intends to exemplify how a design-based research (DBR) methodology can be used to put theory into practice by reporting on a first research cycle of a larger DBR project in the context of upper secondary CLIL history education in Austria.  The project aims to identify design principles of teaching techniques and materials which both support the acquisition of subject-specific competences and language. To this end, this study draws on Dalton-Puffer's (2013) construct of Cognitive Discourse Functions (CDFs), comprising seven key categories of academic language functions which have also been shown to be closely linked to historical competences.  In the course of this study, the researcher and a collaborating teacher systematically developed CDF-based history materials, which were then applied in the classroom and continuously evaluated, using interviews, observations, and written tasks for data collection.Results of the first research cycle suggest that students lack awareness of possible connections between content and language learning and struggle with expressing complex historical content. Both teacher and students responded positively to the intervention on a general level, but pointed out a number of potential refinements, such as a more continuous and balanced intertwining of content and language.